All of our demise - Foody, Amanda; Herman, Christine Lynn (Foody, Amanda. All of us villains (Series), 2022)
"As the curse teeters closer and closer to collapse, the surviving champions each face a choice: dismantle the tournament piece by piece, or fight to the death as this story was always intended."--